Pengaruh Penggunaan Metode Mind Mapping Dalam Keterampilan Menulis Teks Prosedur Pada Siswa Kelas VII SMP Negeri 1 Siantar Tahun Pembelajaran 2022/2023 - Hanisa Hanisa; Rosmawaty Harahap (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
This study aims to, (1) To find out the skills of writing procedural texts without using the mind mapping method in class VII students of SMP Negeri 1 Siantar in the 2022/2023 Academic Year. (2) To find out the skills of writing procedural texts using the mind mapping method in class VII students of SMP Negeri 1 Siantar in the 2022/2023 Academic Year. (3) To find out the effect of the mind mapping method on the skills of writing procedural texts in class VII students of Siantar 1 Middle School in the 2022/2023 Academic Year. The population in this study was students from VII SMP Negeri 1 Siantar with a sample size of 30 students using the Mind Mapping method. The instruments used in this study were writing procedural text contents, writing procedural text structures, writing procedural text writing rules and language features of procedural texts. The method used in this research is one group pretest-posttest. Data analysis techniques use analysis requirements tests, normality tests, and hypothesis tests. The research results during the pretest obtained an average of 60.47, and were included in the sufficient category. Meanwhile, the results of the posttest research obtained an average score of 88 and were included in the very good category. Through testing the hypothesis, namely tcount > ttable, namely 8.5047 > 2.0484, it can be concluded that there is a significant influence from the use of the Mind Mapping method on the Writing Skills of Procedure Text in Class VII Students of SMP Negeri 1 Siantar.